Good corporate governance, pengungkapan corporate social responsibility dan ukuran perusahaan terhadap nilai perusahaan - Melissa Astuti Pasaribu; Swarmilah Hariani (Jurnal Riset Manajemen dan Bisnis, 2022)
This study aims to determine and prove that the influence of good corporate governance, disclosure of corporate social responsibility, and firm size has implications for the company's values. The sample in this study amounted to 100 from the observation data of the population of 25 companies in the consumer goods manufacturing industry sector listed on the Indonesia Stock Exchange (IDX) in 2016-2019. The sampling technique uses the purposive sampling method. Data analysis techniques use analysis using SPSS version 23. The results of this study show that good corporate governance proxied through the audit committee and for disclosure of corporate social responsibility is positive and not significant to the company's value. At the same time, the firm size has a positive and significant on the value of the company.